A comparative study on the performance of cementitious composites resilient to airfield conditions. (3rd May 2021) - Shill, Sukanta Kumer; Al-Deen, Safat; Ashraf, Mahmud; Elahi, Manjur A.; Subhani, Mahbube; Hutchison, Wayne
Highlights: Different cement composites including geopolymer were exposed to airbase operating conditions. A mix of epoxy, silica fume and cement exhibited the highest resilience to the airfield conditions. Geopolymer can be used for regular pavement construction at army airbases. A relatively higher covering to steel reinforcement is suggested for geopolymer. Abstract: With increasing advancement in military aircraft technology, concrete pavements at Australian airbases have been experiencing premature degradation as manifested by scaling. It occurs progressively on the surface of concrete and causes higher maintenance cost and disruption to aircraft operation. This study elucidates the underlying mechanisms of scaling and recommends some low-cost alternative cementitious composites resilient to the airbase operating conditions. To prepare those cement composites, Portland cement (PC) was treated with epoxy resin, acrylic emulsion (AE) and silica fume (SF). Moreover, fly ash (FA) based geopolymer was fabricated and used as another candidate. The resilience of geopolymer, epoxy-SF-cement, AE-SF-cement, and plain PC mortar (control) are examined after prolonged exposure to reproduced airfield environmental conditions. The exposures conditions are applied cyclically until surface scaling is formed. XRD (X-ray diffraction) and FTIR (Fourier transform infrared spectroscopy) analysis are performed to detect the decomposition of crystal lattices of mineral compounds and the degradation of covalent bonds in the cement composites. Also, changes in microstructures, loss of mass and percentages of decreases in the strength of the cement composites are determined. Scaling is developed on the plain PC mortars at the end of 2 months of exposure. However, no scaling is observed on the geopolymer, epoxy-SF-cement, and AE-SF-cement mortars even after 5 months of exposure. In comparison with all cement composites used in this study, the epoxy-SF-cement mortar retained the highest percentage of the strength and exhibited substantially better resistance to the exposure conditions used. Thus, this study recommends the epoxy-SF-cement composite to repair and rehabilitate scale concrete at military airbases. Besides, geopolymer can be used for regular construction at army airbases to combat the saponification problem noticed at an early age of exposures.